Carcass and meat quality traits of chickens fed diets concurrently supplemented with vitamins C and E under constant heat stress - Zeferino, C. P. [UNESP]; Komiyama, C. M.; Pelícia, V. C. [UNESP]; Fascina, V. B. [UNESP]; Aoyagi, M. M. [UNESP]; Coutinho, L. L.; Sartori, J. R. [UNESP]; Moura, A. S.A.M.T. [UNESP] (Elsevier, 2016)
The objective of this study was to determine if a diet supplemented simultaneously with vitamins C and E would alleviate the negative effects of heat stress, applied between 28 and 42 days of age, on performance, carcass and meat quality traits of broiler chickens. A total of 384 male broiler chickens were assigned to a completely randomized design, with a 2×3 factorial arrangement (diet with or without vitamin supplementation and two ambient temperatures plus a pair-feeding group) and 16 replicates. Chickens were kept in thermoneutral conditions up to 28 days of age. They were then housed in groups of four per cage, in three environmentally controlled chambers: two thermoneutral (22.5 and 22.6°C) and one for heat stress (32°C). Half the chickens were fed a diet supplemented with vitamins C (257 to 288 mg/kg) and E (93 to 109 mg/kg). In the thermoneutral chambers, half of the chickens were pair-fed to heat stressed chickens, receiving each day the average feed intake recorded in the heat stress chamber in the previous day. Meat physical quality analyses were performed on the pectoralis major muscle. No ambient temperature×diet supplementation interaction effects were detected on performance, carcass, or meat quality traits. The supplemented diet resulted in lower growth performance, attributed either to a carry-over effect of the lower initial BW, or to a possible catabolic effect of vitamins C and E when supplemented simultaneously at high levels. Heat stress reduced slaughter and carcass weights, average daily gain and feed intake, and increased feed conversion. Growth performance of pair-fed chickens was similar to that of heat stressed chickens. Exposure to heat stress increased carcass and abdominal fat percentages, but reduced breast, liver and heart percentages. Pair-fed chickens showed the lowest fat percentage and their breast percentage was similar to controls. Heat stress increased meat pH and negatively affected meat color and cooking loss. In pair-fed chickens, meat color was similar to the heat stressed group. Shear force was not influenced by heat stress, but pair-fed chickens showed the tenderest meat. In conclusion, reduction in growth performance and negative changes in meat color in heat stressed chickens were attributed to depression in feed intake, whereas negative changes in body composition, higher meat pH and cooking loss were credited to high ambient temperature per se. Diet supplementation with vitamins C and E as antioxidants did not mitigate any of these negative effects.
Keywords: broiler; heat stress; Keywords antioxidants; pair-feeding; tenderness